Legal Analysis of the Prohibition on Female Civil Servants Becoming Second Wives in Polygamous Marriages: A Case Study of Decision No. 7/Pdt.G/2017/PA.BATG - Naila Zikirach Br Lubis; Mochammad Erwin Radityo; Dina Andiza (Fox Justi : Jurnal Ilmu Hukum, 2025)
This research analyzes the legal basis and implications of the prohibition on female civil servants becoming second wives in polygamous marriages, with a focus on decision no. 7/pdt.g/2017/pa.batg. The study aims to explore the intersection between marital rights, gender equality, and administrative regulations within the indonesian legal system. Using a normative legal method combined with a case approach, the research examines relevant laws including law no. 1 of 1974 on marriage, government regulation no. 45 of 1990 on amendments to regulation no. 10 of 1983 concerning marriage for civil servants, and other related legal instruments. The findings show that the prohibition is rooted in efforts to maintain professional integrity, institutional discipline, and gender equity in the public sector. However, the enforcement of such restrictions raises constitutional questions regarding equal rights and personal freedom. The case of decision no. 7/pdt.g/2017/pa.batg highlights the tension between individual marital choices and institutional norms. This research concludes that while the regulation seeks to uphold ethical standards in public service, it also requires harmonization with fundamental human rights principles to ensure justice and legal certainty.